2001
DOI: 10.1063/1.1407303
|View full text |Cite
|
Sign up to set email alerts
|

Single sharp spot in fluorescence microscopy of two opposing lenses

Abstract: We demonstrate theoretically, experimentally, and in an imaging application the possibility to generate a single predominant sharp diffraction maximum in the effective point-spread function of a fluorescence microscope that coherently uses two opposing lenses. This is achieved through binary pupil filters that preclude the origination of the unfavorable strong interference side maxima that are otherwise present in these systems. Mathematical postprocessing, which has so far been a prerequisite to gain artifact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…In addition the fluorescence from the more remote parts of the focus is further suppressed by the confocal pinhole. Using oil immersion lenses of a nominal NA of 1.4, we have recently succeeded in suppressing the lobes down to 12% [6]. It is clear that a larger aperture angle a max increases the discrepancy between the spatial frequency of the inner and outer standing wave.…”
Section: Dark Ring 4pi-confocal Microscopymentioning
confidence: 95%
See 1 more Smart Citation
“…In addition the fluorescence from the more remote parts of the focus is further suppressed by the confocal pinhole. Using oil immersion lenses of a nominal NA of 1.4, we have recently succeeded in suppressing the lobes down to 12% [6]. It is clear that a larger aperture angle a max increases the discrepancy between the spatial frequency of the inner and outer standing wave.…”
Section: Dark Ring 4pi-confocal Microscopymentioning
confidence: 95%
“…The creation of a predominant spot with dimensions much smaller than that of the confocal microscope using only a single wavelength has not been attained until very recently [6]. Analyzing the problem theoretically and experimentally, we found that a simple ring-shaped blocking filter placed into the illumination wavefronts of a two-photon excitation 4Pi-confocal microscope redistributes the focal energy in such a way that the excitation power of the lobes is scattered throughout the focal region, while leaving that of the main maximum unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach has been recently reported in the socalled selective plane illumination microscopy (Huisken et al, 2004). In 4Pi-confocal microscopes (Blanca et al, 2001), two opposing, high-NA objectives are used to coherently illuminate the fluorescent sample and, therefore, to create an axially-narrowed interferencial focal spot. The stimulated emission depletion microscopy (Klar et al, 2001) uses the inhibition of fluorophores at the outer region of the scanning excitation spot to break the diffraction barrier of this stretching.…”
Section: Introductionmentioning
confidence: 95%
“…Due to these sidelobes the single-photon 4Pi technique does not provide useful images. Nevertheless, by use of two-photon excitation the sidelobes are removed and therefore the technique provides high quality 3D images [5]. An alternative technique to reduce the PSF anisotropy is based on the use of pupil filters.…”
Section: Introductionmentioning
confidence: 99%